Collocation of hydrological and biological attenuation of nitrate in an urban stream. Issue 17 (13th April 2016) - Klein, Trevor; Toran, Laura
Abstract: The hydrologic and biogeochemical processes that control nutrient export in urban streams are not well understood. Attenuation can occur by tributary dilution, groundwater discharge, and biological processing both in the water column and the hyporheic zone. A wastewater treatment plant on Pennypack Creek, an urban stream near Philadelphia, PA, provided high nitrate concentrations for analysis of downstream attenuation processes. Longitudinal sampling for an 8‐km reach revealed decreases in nitrate concentration of 2 mg l −1 at high flow and 4.5 mg l −1 during low flow. During high flow, δ 15 N‐NO3 increased from 9.5 to 10.5‰ and during low flow increased from 10.1 to 11.1‰. Two reaches were sampled at fine spatial intervals (approximately 200 m) to better identify attenuation processes. Mixing analysis indicated that groundwater discharge and biological processing both control nitrate concentration and isotope signatures. However, fine‐scaled sampling did not reveal spatially discrete zones; instead, these processes were occurring simultaneously. While both processes attenuate nitrate, they have opposite isotope signatures, which may have muted changes in δ 15 N‐NO3 . At high flow, a decrease in Cl/NO3 ratios helped distinguish groundwater discharge occurring along both finely sampled reaches. At low flow, biological processing seemed to be occurring more extensively, but the δ 15 N‐NO3 signature was not consistent with either a single process or a sequential combination of groundwater dilution and biological nitrate attenuation. The collocation of processes makes it more difficult to assess biological processing hot spots and predict how urbanization and subsequent stream restoration influence nitrate attenuation. Copyright © 2016 John Wiley & Sons, Ltd.